Epitopes for Multivalent Vaccines Against Listeria, Mycobacterium and Streptococcus spp: A Novel Role for Glyceraldehyde-3-Phosphate Dehydrogenase - Alvarez-Dominguez, Carmen; Salcines-Cuevas, David; Teran-Navarro, Héctor; Calderon-Gonzalez, Ricardo; Tobes, Raquel; Garcia, Isabel; Grijalvo, Santiago; Paradela, Alberto; Seoane, Asunción; Sangari, Felix J.; Fresno, Manuel; Calvo-Montes, Jorge; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
The glycolytic enzyme and bacterial virulence factor of Listeria monocytogenes, the glyceraldehyde-3-phosphate dehydrogenase (GAPDH, Lmo2459), ADP-ribosylated the small GTPase, Rab5a, and blocked phagosome maturation. This inhibitory activity localized within the NAD binding domain of GAPDH at the N-terminal 1–22 peptides, also conferred listeriosis protection when used in dendritic cell-based vaccines. In this study, we explore GAPDH of Listeria, Mycobacterium, and Streptococcus spp. taxonomic groups to search for epitopes that confer broad protection against pathogenic strains of these bacteria. GAPDH multivalent epitopes are selected if they induce inhibitory actions and wide-ranging immune responses. Proteomic isolation of GAPDH from dendritic cells infected with Listeria, Mycobacterium, or Streptococcus confirmed similar enzymatic, Rab5a inhibitory and immune stimulation abilities. We identified by bioinformatics and functional analyses GAPDH N-terminal 1–22 peptides from Listeria, Mycobacterium, and Streptococcus that shared 95% sequence homology, enzymatic activity, and B and T cell immune domains. Sera obtained from patients or mice infected with hypervirulent pathogenic Listeria, Mycobacterium, or Streptococcus presented high levels of anti-GAPDH 1–22 antibodies and Th2 cytokines. Monocyte derived dendritic cells from healthy donors loaded with GAPDH 1–22 peptides from Listeria, Mycobacterium, or Streptococcus showed activation patterns that correspond to cross-immunity abilities. In summary, GAPDH 1–22 peptides appeared as putative candidates to include in multivalent dendritic based vaccine platforms for Listeria, Mycobacterium, or Streptococcus.